Influence of Foliar Application of some Micronutrients on Maize Kernel Yield and Nutrient content - Mustafa, Razhan Bakr; Rasul, Ghafoor Ahmed Mam (Sulaimani Journal for Pure and Applied Sciences, 2020)
The present study was conducted to evaluate the effect of various levels of some micronutrients Zn, Fe and Cu individually and in combination on maize (Zea mays L.) kernel yield and kernel content of micronutrients using foliar application. The field experiment was behaved at Qlyasan Agricultural Research Farm in the Sulaimani Governorate of the Kurdistan Region of Iraq from April to August 2019. The experimental treatments laid out in a complete randomized block design (RCBD) with three replicates. The treatments were included three levels of Zn (2, 4 and 6 kg ha-1), three levels of Fe (3, 5 and 7 kg ha-1) and three levels of Cu (2, 3 and 4 kg ha-1) as individual and three levels of combined Zn + Fe + Cu (2 +3 + 2 kg ha-1), Zn + Fe + Cu (4 + 5 + 3 kg ha-1) and Zn + Fe + Cu (6 + 7 + 4 kg ha-1) with control. The results revealed that the foliar application of some micronutrients significantly affected in kernel yield of maize and the uptake of applied micronutrients by maize kernel at (P≤0.05). The maximum kernel yield of maize was 12.63 Mg ha-1 obtained with the application of Zn (2 kg ha-1) (T2) along with recommended NPK. Also, the results showed that the foliar feeding affected significantly of micronutrient uptake by the kernel of maize plant, the maximum values of micronutrient uptake by maize kernel for Zn, Fe and Cu were 2.95 kg ha-1, 9.25 kg ha-1 and 4.94 kg ha-1 from the treatments T12, T12 and T6 respectively.
Keywords: Foliar application; Maize; Zinc; Iron; Copper